When mayors take charge school governance in the city - Viteritti, Joseph P., 1946-; ebrary, Inc. (Washington, D.C. : Brookings Institution Press, 2009)
"Assesses the results of mayoral control nationwide, detailing the experience in three key cities: Boston and Chicago, the major prototypes for mayoral control, and Detroit, where mayoral control was not successful. Also provides the first in-depth examination of New York City, where the law installing mayoral control sunsets in 2009"--Provided by publisher.
Why governance matters / Joseph P. Viteritti -- General overviews -- Mayoral control : what we can and cannot learn from other cities / Jeffrey R. Henig -- Mayoral control of schools : politics, trade-offs, and outcomes / Michael W. Kirst -- Does mayoral control improve performance in urban districts? / Kenneth K. Wong -- City case studies -- Governing the Boston public schools : lessons in mayoral control / John Portz and Robert Schwartz -- Updating tradition : the institutional underpinnings of modern mayoral control in Chicago's public schools / Dorothy Shipps -- Who's afraid of a mayoral takeover of Detroit public schools? / Wilbur C. Rich -- The New York experience -- A history of public school governance in New York City / Diane Ravitch -- Parent power and mayoral control : parent and community involvement in New York City schools / Clara Hemphill -- New York : past, present, future / Joseph P. Viteritti.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: School districts -- United States -- Administration -- Case studies; Urban schools -- United States -- Administration -- Case studies; Public schools -- United States -- Administration -- Case studies; Electronic books